Complexos de rutênio bioativos: síntese, caracterização e ensaios biológicos - Cardoso, Carolina Riverin (2014)
Ru(II) polypyridyl anticancer compounds is drawing increasing attention to drug development. The luminescence of this type of complex open wide possibilities of using molecular systems in biological applications. Herein we investigated, the synthesis, characterization and biologic studies of the complex cis-[Ru(LL) 2L2]2+ where, L-L = 2,2-bipyridine (bpy) and phen = 1,10-phenanthroline (phen) and L = imidazole (ImH) and 1-methyl-imidazole (1MeIm). The complexes which can be easily prepared are stable in solid state and in water solution (without light) and resistant to hydrolysis at pH range from 2 to 10. The complexes display strong absorption in the visible region (490 nm, ε = 15000 mol-1Lcm-1) and an intense and long lived emission at 660 nm with a large Stokes shift (5500 cm-1). Spectroscopic (CD, STD-NMR and DOSY-NMR) and ITC studies indicate binding of cis-[Ru(phen)2(ImH)2]2+ and HSA occurs via non-covalent interactions. Accordingly, the complexes showed marked cell proliferation inhibition against the cancer cells HCT116p53+/+, HCT116p53-/- and A2780 with IC50 values below 10 μmol L-1. The Complex induces G1 cell arrest in both cells although it is more expressive in P53+/+ and activates the proapoptotic protein PARP in only p53-/- suggesting diferent pathway with p53- dependent and p53-independent modes of action. The complexes presents unique features for potential diagnostic and therapeutic applications of cancer.